Avenida Goiás: lugar, monumento e memória - Oliveira, Irina Alencar de (2015)
It is proposed to research the urban permanences verified in the initial core of Goiânia, as from Goiás Avenue, its most symbolic and expressive stretch. It starts with the analysis of the political discourse disseminated by Pedro Ludovico Teixeira, in favor of moving the capital to a place better adjusted to his political interests, after the triumph of the Brazilian Revolution of 1930. Therefore, he builds powerful social representations, based on the images of the old and the new capital, in order to oppose those against this change and consolidate his government. In addition to the speech and propaganda, Ludovico uses, as a statement element, the urban plan designed by Attilio Corrêa Lima, creating a modern intentional monument to be immortalized, translated by the monumental Goiás Avenue. Then, the city experiences a vertiginous growth in its territory and population, mainly after the 1950s, resulting in the disfigurement of its pioneering core. The spatial transformations verified in Goiás Avenue are representative of this scenario, such as its verticalization process and the changes in its layout to meet the demands from the public transportation. From these losses, consequences of the progressive mentality that is rooted in the local culture, arise the first initiatives to preserve the material evidences of the beginning Goiânia, culminating with its federal preservation in 2003. From this institutionalization as a national heritage, it is focused the appropriation by the city inhabitants, through the research of the urban imaginary created since the pioneer’s city until the present day, highlighting striking points in this trajectory. For that, it is used literature in prose and verse to reach the local collective memory, focusing on the capital early years and on the current city - violent, disjointed and that is forgetting its history day by day.